A Novel Circular RNA CircRFX3 Serves as a Sponge for MicroRNA-587 in Promoting Glioblastoma Progression via Regulating PDIA3 - Li, Tong; Xu, Jianguo; Liu, Yi (Frontiers in Cell and Developmental Biology, 2021)
Growing studies indicated that circular RNAs (circRNAs) take parts in the progression of numerous tumors. However, the functions of circRNAs in glioblastoma (GBM) remains largely unknown. In this study, we focused on a novel circRNA (hsa_circ_0001836) which was spliced from RFX3. Therefore, it was named circRFX3. We confirmed that the expression of circRFX3 was prominently raised in GBM cell lines and clinical GBM tissues. The results of a series of overexpression and knockdown assays indicated that circRFX3 could boost the proliferation, invasion and migration of GBM cells. By performing dual-luciferase reporter gene and RNA pull-down assays, we verified that circRFX3 could sponge microRNA-587 (miR-587) to exercise its function of competing endogenous RNA (ceRNA)in the development of GBM. In addition, PDIA3 was proved to be a downstream target of miR-587 and regulate Wnt/β-catenin pathway. In conclusion, circRFX3 could act as a cancer-promoting circRNA to boost the development of GBM and regulate the miR-587/PDIA3/β-catenin axis. It might provide the treatment of GBM with a novel target of molecular therapy.